Symptoms and Antireflux Medication Use Following Laparoscopic Nissen Fundoplication: Outcome at 1 and 4 Years - Bloomston, Mark (Society of Laparoendoscopic Surgeons, 2003)
BACKGROUND: We have reported 1-year outcomes and antacid medication use in 100 patients undergoing laparoscopic Nissen fundoplication. As a follow-up study, we queried these same patients to determine whether their outcomes endured 4 years after fundoplication. METHODS: One hundred patients undergoing laparoscopic Nissen fundoplication between 1992 and 1997 were asked, at 1 to 2 years and 4 to 6 years postoperatively, to grade their symptoms on a scale of 1 (mild) to 10 (severe). Patients were also queried as to the number/cost of antacid medications used before and after fundoplication. RESULTS: Significant improvements were noted in symptoms of heartburn, postprandial emesis, gas/bloating, and dysphagia after fundoplication. Significant decreases in antacid medication use (97%vs 19%) and monthly costs ($168±$91 vs $30±$54) were seen following fundoplication. The number of patients on antacid medications and the monthly costs of these medications (37%and $53±$87, respectively) increased significantly from early to late follow-up, but were still significantly lower than those before surgery. Overall, 87%and 90%of patients were pleased with their outcome at early and late follow-up, respectively, and 93%and 92%of patients stated they would consider undergoing fundoplication again if necessary (P=NS). CONCLUSION: Laparoscopic Nissen fundoplication results in a significant reduction in the symptoms of reflux and the use of antacid medications with a high degree of patient satisfaction. Although some patients return to antacid medications at late follow-up, they continue to have few symptoms and are pleased with their outcomes.